The foreign policy of South Korea towards Japan: The colonial past in the contemporary dynamics of the Park Geun-Hye, Moon Jae-In, and Yoon Suk-Yeol administrations - Dias, Mauricio Luiz Borges Ramos [UNESP] (Univ Externado Colombia, Dept Publicaciones, 2025)
Permeated by traumatic memories and claims for recognition and compensation of the colonial past, the bilateral relationship between South Korea and Japan experienced intense strains during the administrations of Park Geun-hye (2013-2017) and Moon Jae-in (2017-2022). Park stipulated that recognition of the colonial past would be a prerequisite for improving relations with Tokyo, and the Comfort Women Agreement, unexpectedly signed, had its legitimacy challenged. During his term, Moon invalidated the Comfort Women Agreement and demanded a resolution centered on the demands of the victims, while also advocating for Japanese companies to compensate South Koreans forced to work in its facilities during the colonization. In a different panorama, the conservative government of Yoon Suk-yeol (2022-present) adopted a stance of restructuring the South Korea-Japan relations without criticizing the effects of colonization or seeking Japan's acknowledgment of responsibility. This research analyses how the administrations of Park, Moon, and Yoon have handled the colonial agenda in South Korea's foreign policy, resulting in either friction or rapprochement with Japan. It is argued that Park intensified historical grievances, even after the Comfort Women Agreement, due to its unsatisfactory approach. Moon, focused on healing the colonial wounds, faced diplomatic, economic and security friction amid Japan's unwillingness to revisit the past. Lastly, Yoon, in seeking reconciliation with Japan, achieved rapprochement in a tone of submission, undermining the victims' claims for justice.
Keywords: Colonial disputes; Park Geun-hye; Moon Jae-in; Yoon Suk-yeol; Japan